2022
DOI: 10.3389/fmolb.2022.1005136
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-dependent adaptor molecule recruits DNA methyltransferase to the TLR4 gene in colonic epithelial cells to suppress inflammatory reactions

Abstract: The intestine is inhabited by a large number of commensal bacteria that are immunologically non-self, potentially causing inflammation. However, in a healthy intestine, inflammation is strictly controlled at low levels to maintain homeostasis. We previously reported that the gut microbiota induce DNA methylation of the gene encoding Toll-like receptor (TLR) 4, a pattern recognition receptor that recognizes lipopolysaccharides of gram-negative bacteria, in colonic epithelial cells, suggesting its role in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These genes are likely linked to autoimmune skin diseases and inflammatory skin conditions 67,68 Epigenetic regulation and gene expression: HDAC5 and RBM14 are involved in epigenetic modifications and gene regulation, potentially influencing a range of skin processes, such as aging, development and differentiation 69,70 Cell signalling and cytoskeletal remodelling: NCK1 and CBY1 play roles in cell signalling and cytoskeletal remodelling, which are crucial for preserving the structural integrity and functionality of skin cells. Cellular processes and transport: DCTN1 and MYO19 participate in cellular processes, such as protein transport and organelle movement.…”
Section: Resultsmentioning
confidence: 99%
“…These genes are likely linked to autoimmune skin diseases and inflammatory skin conditions 67,68 Epigenetic regulation and gene expression: HDAC5 and RBM14 are involved in epigenetic modifications and gene regulation, potentially influencing a range of skin processes, such as aging, development and differentiation 69,70 Cell signalling and cytoskeletal remodelling: NCK1 and CBY1 play roles in cell signalling and cytoskeletal remodelling, which are crucial for preserving the structural integrity and functionality of skin cells. Cellular processes and transport: DCTN1 and MYO19 participate in cellular processes, such as protein transport and organelle movement.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of epigenetic modifications, such as DNA methylation, histone modifications, and non-coding RNAmediated regulation, can contribute to the development and progression of NAFLD [52]. More recently, gut microbiota have been identified as important factors that significantly influence the host epigenetic landscape in NAFLD pathogenesis [49][50][51][53][54][55][56], highlighting the need for further research in this area to develop new therapeutic strategies. Gut microbiota can modulate the host's epigenetic landscape in the context of NAFLD through various mechanisms.…”
Section: Impact Of Microbiota-host Crosstalk On Epigenetic Modificati...mentioning
confidence: 99%
“…Recent research has revealed that the gut microbiota can modulate the host's epigenetic landscape through bacterial components and microbial metabolites. Dysbiosis of gut microbiota may lead to aberrant epigenetic modifications, such as DNA methylation and histone modifications, which can affect gene expression and contribute to the pathogenesis of NAFLD [ 49 , 50 , 51 ]. Therefore, in this review, we will focus on the evidence suggesting that the gut microbiome influences the pathogenesis of NAFLD by manipulating epigenetic mechanisms.…”
Section: Nafld and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…TLRs, for example, were initially discovered for their role in the host development ( Anthoney et al 2018 ). Signalling through TLR4, which recognises one of the most potent inducers of innate immunity, LPS, suppresses inflammatory reactions in colonic epithelial cells ( Narabayashi et al 2022 ). The same type of signalling via LPS from the gut commensal Bacteroides vulgatus , with a weak agonistic activity, extinguishes intestinal inflammation and restores gut immune homeostasis ( Steimle et al 2019 ).…”
Section: Eukaryotic Innate Immunity Receptorsmentioning
confidence: 99%